Enhancing Quranic Literacy Through The Quran Waqf Program: A Case Study In Sidomulyo, Lamongan - Khusnan, Ach; Yuliani, Naning; Nikmatul, Khoirun; Anggi, Putri; Noor, Akbar (PUDAK: Local Wisdom Community Journal, 2024)
The condition of the Qur'an in several mosques in Sidomulyo Village appears to be in inadequate condition. Prayer equipment appears to need to be renovated, the cover of the Qur'an has been removed, or its contents are scattered on a pile of other Qur'ans. The productivity of the Sidomulyo Village community in gaining religious knowledge has limitations in the management of the mosque. This condition can certainly reduce the devotion of the community in worship. This program aims to help prosper the mosque by providing devotion to the community who worship and gain religious knowledge in mosques in Sidomulyo Village. The Al-Quran waqf program not only focuses on providing holy books, but also on empowering the community to improve understanding and practice of the teachings of the Qur'an. This approach is expected to create significant and sustainable changes in the religious quality of the village community. The success in resolving this problem was supported by several factors, including: (1) Collaboration between KKN Institut Al Azhar with STIBA AR Raayah which sponsored the Al-Quran distributed in the Al-Quran and Prayer Equipment Waqf program "Together Building the Spirit of Rahmatan Lil'Alamin", (2) Enthusiasm from the community and support from the local government in accepting waqf for mosques in Sidomulyo village.